Mobilising Stoke: A Genealogy of Surf Tourism Development in Miyazaki, Japan. Issue 1 (2nd January 2018) - Doering, Adam
ABSTRACT: This article presents a genealogy of domestic surf tourism development in contemporary Japan. Drawing on two months' ethnographic fieldwork conducted between July and August 2016, and participant observation during three years working, living and surfing in the area, I trace the historical production of one of Japan's most prominent surf tourism destinations, Miyazaki Prefecture. Detailing the convergence of surfing culture and tourism development from 1930 to 2016, I examine how surf tourism came to be mobilised in Miyazaki as a tool for revitalising the local economy. The article then addresses three important transformations of the Japanese seascape surf tourism development invites: the feminisation of surf capital, global cultural gentrification and the reinforcement of urban–rural disparities. The article concludes with a reflection on how surf tourism development may (dis)connect local surfing communities and identify areas for future research concerning surf destination development leading up to the Tokyo 2020 Olympics.